Cooperaç\~ao brasileira para o desenvolvimento internacional (COBRADI): O brasil e os fundos multilaterais de desenvolvimento - Manuel Jose Forero Gonzalez; Ricardo Mendes Pereira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– According to the survey by the Institute of Applied Economic Research (IPEA) in collaboration with the Brazilian Agency for Cooperation (ABC), Brazil contributed during the period of 2005-2009, with funds for International Development in the order of R 3.2 billion. Of the total budget for Brazilian Cooperation for International Development (COBRADI), R 929.7 million, almost 30%, corresponded to contributions to multilateral development funds such as the International Development Association (IDA) of the World Bank, the Fund for Special Operations (FSO) of the Inter-American Development Bank and the African Development Fund (ADF) of the African Development Bank. This paper seeks to describe the role of these institutions, their priorities, funding conditions and the Brazilian contribution throughout their participation as shareholders. Likewise, it seeks to launch for discussion a few elements present in the current debate on the quality of aid offered by those institutions that provide resources for the development of the poorest countries in the world, within highly concessional terms and to which Brazil has allocated a significant portion of their contributions during the period.
Keywords: F35; 330